Ethnic plurality and nation in Peru in Mariátegui's essays - Dancourt, Carlos (2006)
It is known that, since the end of the 19th century, the thought of the Peruvian elites is determined by the reflection on the unity and destiny of the country. Peru's defeat by Chile, and the accompanying ethnic riots and violence, have revealed the extreme weakness of the nation.